La recherche en temps réel : projet ECHO pour francophones - Détermination des besoins des fournisseurs de services desservant les communautés franco-ontariennes afin de créer un programme de formation en français sur le traitement des dépendances - CAMH-Evidence Exchange Network (2023)
fs-ref-orig: CAMH-Evidence Exchange Network. (2023). La recherche en temps réel : projet ECHO pour francophones - Détermination des besoins des fournisseurs de services desservant les communautés franco-ontariennes afin de créer un programme de formation en français sur le traitement des dépendances. https://kmb.camh.ca/fr/eenet/documentation/la-recherche-en-temps-reel-projet-echo-pour-francophones fs-code-orig: CAMH-Evidence Exchange Network-2023a

Research as it Happens : ECHO project for Francophones - Assessing the needs of service providers working with Franco-Ontarian communities to create a French-language, substance use management training program - CAMH-Evidence Exchange Network (2023)

La santé des francophones en situation minoritaire au cœur de nos actions - Cardinal, Dominique; Borris, Caroline; Pinet, Bernard; Leclair, F. (Reflets, 2018)
Au Canada, plus d’un million de francophones habitent à l’extérieur du Québec, parmi lesquels 35 % rapportent avoir peu ou aucunement accès à des services de santé dans leur langue (Gagnon-Arpin, et collab., 2014). En vue de contrer les défis de la santé dans les communautés francophones en situation minoritaire (CFSM), le Consortium national de formation en santé — Volet Université d’Ottawa a développé plusieurs pratiques prometteuses en matière de soutien aux futurs étudiants et étudiantes, à la population étudiante inscrite aux programmes ciblés par le CNFS ainsi qu’aux professionnelles et professionnels, chercheuses et chercheurs du domaine de la santé. Divers programmes sont mis à profit pour soutenir la génération et la diffusion des connaissances. Ces initiatives ainsi que leurs retombées positives méritent l’attention de tous les partenaires qui ont à coeur la santé des francophones.

Welsh in the health service: The scope, nature and adequacy of Welsh language provision in the National Health Service in Wales. Consumer Council Wales. - Misell, Andrew (2000)
The Welsh Consumer Council set about defining the consumer interest in language in its 1996 report, Welsh as a Consumer Issue. That report emphasised how and why the opportunities for using the Welsh language be considered from the view of the consumer. In general, service providers are well equipped to look after their own interests – the consumer by comparison is often weak. It is this theme that is picked up in this report – Welsh in the Health Service: The Scope, Nature and Adequacy of Welsh Language Provision in the National Health Service in Wales. While the report recognises that, in many instances, Welsh language service provision is about providing equal opportunities and ensuring a high quality, consumer sensitive service, it also identifies groups for whom service provision in the first language is a clinical necessity. The report concludes that in the case of Welsh-speaking patients, there are instances when they cannot be treated effectively except in their first language, or in both their languages. This is especially true in the case of those receiving speech and language therapy, and for the following key groups: - people with mental health problems. - people with learning disabilities and other special needs. - older people, and - young children. The report contains many recommendations and calls for a fundamental change of approach on the part of the NHS in Wales.
Nombres de pages: 85